Visiting Albert and Rose Watkins And Friends in Southern California - Watkins, Howard::::::::: (1983)
Pat Motts, Irma Frankl, Rose Watkins holding Robin Watkins, Adam Watkins on couch Rose baby sat Irma's two sons in the late 1930's